MALAT1 knockdown alleviates the pyroptosis of microglias in diabetic cerebral ischemia via regulating STAT1 mediated NLRP3 transcription - Nan Zhao; Wei Hua; Qi Liu; Yueying Wang; Zhiyi Liu; Sinan Jin; Benshuai Wang; Yuxin Pang; Jiping Qi; Yuejia Song (Molecular Medicine, 2023)
Abstract Background Dysregulated long non-coding RNAs participate in the development of diabetic cerebral ischemia. This study aimed to investigate the underlying mechanism of lncRNA MALAT1 in diabetic cerebral ischemia. Method Middle cerebral artery occlusion (MCAO) was performed to establish diabetic cerebral I/R in vivo. TTC and neurological deficits assessment were performed to assess cerebral ischemic injury. LDH was conducted to detect cytotoxicity. RT-qPCR and western blotting assays were applied to determine mRNA and protein expression. Flow cytometry was performed to detect the pyroptosis of BV2 cells. Immunofluorescence and FISH were conducted for subcellular localization of MALAT1 and STAT1. ELISA was performed to determine cytokine release. Dual luciferase reporter, RIP, and ChIP assays were used to validate the interaction between STAT1 and MALAT1/NLRP3. Diabetes aggravated cerebral injury in vivo and in vitro. Diabetic cerebral ischemia induced inflammatory response and inflammation-induced cell pyroptosis. Result MALAT1 was overexpressed in diabetic cerebral ischemia models in vivo and in vitro. However, knockdown of MALAT1 suppressed inflammatory response and the pyroptosis of BV2 cells. Moreover, MALAT1 interacted with STAT1 to transcriptionally activate NLRP3. Knockdown of STAT1 significantly reversed the effects of MALAT1. Furthermore, STAT1 promotes the MALAT1 transcription. MALAT1 interacts with STAT1 to promote the pyroptosis of microglias induced by diabetic cerebral ischemia through activating NLRP3 transcription. Conclusion Thus, knockdown of MALAT1 may be a potential promising therapy target for diabetic cerebral ischemia.